A prospective observational cohort study of lenvatinib as initial treatment in patients with BCLC-defined stage B hepatocellular carcinoma - Satoshi Kobayashi (BMC Cancer, 2022)
Abstract Background Transarterial chemoembolization (TACE) is the standard treatment for intermediate stage hepatocellular carcinoma (HCC) (Barcelona Clinic Liver Cancer [BCLC] B). However, it often leads to a poor prognosis and decreased hepatic function especially in patients with BCLC substage B2. Lenvatinib (LEN) was demonstrated to be efficacious in these patients in the REFLECT phase 3 trial. We therefore aimed to evaluate the efficacy and safety of LEN as a first-line treatment for the patients with HCC at BCLC substage B2. Methods This prospective observational study used LEN in TACE-naïve patients with HCC at BCLC substage B2 and preserved hepatic function. The primary endpoint was overall survival. A one-year survival rate threshold of 60% and an expected survival rate of 78%, based on previous reports of TACE, was assumed for setting the sample size. With a one-sided α-type error of 5% and 70% detection power, 25 patients were required over a 2-year enrollment period and 10-month follow-up period. Results Thirty-one patients were enrolled in this study from June 2018 to June 2020. The 1-year survival rate was 71.0% (90% confidence interval, 68.4–73.6%). Median overall and progression-free survival periods were 17.0 and 10.4 months, and the objective response rates according to Response Evaluation Criteria in Solid Tumor (RECIST) version 1.1 and modified RECIST criteria were 22.6% and 70.0%, respectively. Common adverse events (AEs) were fatigue (68%), hypertension (65%), anorexia (61%), palmar-plantar erythrodysesthesia (39%), and thrombocytopenia (32%) of any grade; aspartate aminotransferase increased (23%), alanine aminotransferase increased (16%), and grade ≥ 3 proteinuria (13%). Treatment interruption and dose reduction were required in 61% and 81% of patients, respectively. LEN was discontinued in 29 patients due to disease progression (n = 17), AEs (n = 9), conversion to curative treatments (n = 2), and sudden death (n = 1), whereas post-LEN treatments were administered in 18 patients, including systemic chemotherapy (n = 11), TACE (n = 6), transarterial infusion (n = 1) and clinical trial (n = 1). Conclusions The results suggest that LEN provides treatment benefits as an initial therapeutic in patients with BCLC substage B2 HCC with a safety profile comparable to that previously reported.